Growth and optical properties of CaxCoO2 thin films - Binbin Xin; Arnaud Le Febvrier; Lei Wang; Niclas Solin; Biplab Paul; Per Eklund (Materials & Design, 2021)
The layered cobaltates AxCoO2 (A = Li, Na, Ca, Ba, Sr) are of interest for energy applications such as thermoelectrics and batteries. However, it is challenging to obtain these phases in pure from as thin films. Here, phase-pure CaxCoO2 (x ~ 0.5) thin films were obtained by annealing of Ca(OH)2/Co3O4 multilayers made by moisture treatment of sputter-deposited CaO/Co3O4 multilayer films. The pure CaxCoO2 thin films exhibit an average optical transmittance of approximately 36% in the visible region and greater than 70% in the near-infrared (NIR) region. In addition, the electrical conductivity can be increased by incorporating a secondary Ca3Co4O9 phase into the CaxCoO2 thin film without large changes in optical properties and Seebeck coefficient.